Lectures on solar physics: [based on a Workshop on Solar Physics] - Antia, H. M.; Bhatnagar, Arvind; Ulmschneider, Peter (Lecture notes in physics, 2003)
This volume has grown out of lectures addressing primarily graduate students and researchers working in related areas in both astrophysics and space sciences. All contributions are self-contained and do not require prior in-depth knowledge of solar physics. The result is a unique textbook that fulfills the needs of those wishing to have a pedagogic exposition of solar physics bringing them up-to-date in a field full of vitality and with exciting research
Keywords: Konferenzschrift; Physik; Sonne